Slow-wave sleep is associated with nucleus accumbens volume in elderly adults - Kitti Bán; Ádám Nárai; Noémi Báthori; Éva M. Bankó; Adél Bihari; Vivien Tomacsek; Tibor Kovács; Béla Weiss; Petra Hermann; Péter Simor; Zoltán Vidnyánszky (NeuroImage)
Slow-wave sleep (SWS) is essential for restorative neural processes and its decline is associated with both healthy and pathological ageing. Building on previous rodent research, this longitudinal study identified a significant association between nucleus accumbens (NAcc) volume and SWS duration in cognitively unimpaired older adults, whilst no significant link was observed between NAcc volume and N2 or rapid eye movement (REM) sleep percentage. Our findings support the involvement of the NAcc in ageing-related modulation of SWS and thus suggest the NAcc as a potential neural marker or therapeutic target for improving SWS.